(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
The article deals with the topical issues of changing the traditional paradigm of teaching future specialists in artistic disciplines in the People’s Republic of China in the era of artificial intelligence. Artificial intelligence is a logical product of the rapid development of information and advanced computer technologies, covering various interdisciplinary subjects, including music disciplines, adding new modern elements and capabilities, which significantly optimizes the process of training future specialists in music disciplines in higher education institutions. The article presents the national legislative and regulatory framework for the regulation of artificial intelligence in Ukraine. The article reveals the main common methods of artificial intelligence: classical, machine learning, artificial neural network, deep learning. The author characterizes popular artificial intelligence technologies: natural language processing, speech understanding, photo recognition and processing, independent intermediaries, human behavior assessment, forecasting, and technical creativity. It is proved that the combination of audio big data, virtual reality, and artificial intelligence allows to realize the function of searching for musical information, promotes the emergence of intelligent electronic musical instruments, and digitizes sound signals that are easy to store and distribute. It is concluded that modern technologies and the era of artificial intelligence are significantly changing the traditional paradigm of teaching future specialists in artistic disciplines. Valuable experience has been gained by Chinese higher education institutions that train such specialists, which can be implemented in the practice of domestic higher education institutions. Prospects for further research are to study the ethical issues of using artificial intelligence in music education.